KONSEP PENDIDIKAN KARAKTER KH. M. HASYIM ASY‘ARI: Studi Kitab Âdâb al-‘Âlim wa al-Muta‘allim - Titik Handayani; Achmad Fauzi (Islamuna: Jurnal Studi Islam, 2019)
Moral decadence that befalls most students in Indonesia is very alarming. The moral values which are expected belong to themselves increasingly decline. It is proven by the brawl among students, pregnant out of wedlock, drug abuse, and the persecution on the teachers significantly increase. By using analytical-descriptive method, this study concerns to the character education in KH. M. Hasyim Asy‘ari’s perspective taken from his book entitled Âdâb al-‘Âlim wa al-Muta‘allim which is focused on the students ethics in studying, including ethics in learning, student’s ethics to the teacher, and student’s ethics in dealing with the lesson. The result of this study shows that character education in KH. M. Hasyim Asy‘ari’s perspective has a harmony even precedes a number of values within character education materials of the Research and Development Agency, Curriculum Center of the Ministry of National Education, Indonesia. Thus, it can be developed within character education discourse that is being carried out and it can produce the knowledgeble students and also having good personalities.[Krisis akhlak karimah yang menimpa mayoritas peserta didik di Indonesia semakin memprihatinkan. Nilai moral yang diharapkan ada dalam diri mereka semakin terkikis, sehingga mengakibatkan tawuran antarpelajar, siswa hamil di luar nikah, penggunaan narkoba semakin merajalela, serta penganiayaan siswa terhadap guru yang bahkan sampai berujung kepada kematian sang guru. Dengan metode analitis-deskriptif, penelitian ini mengkaji tentang pemikiran KH. M. Hasyim Asy‘ari tentang pendidikan karakter dalam Âdâb al-‘Âlim wa al-Muta‘allim yang difokuskan pada etika peserta didik dalam menuntut ilmu, yang mencakup etika dalam belajar, etika siswa terhadap guru, dan etika siswa dalam menghadapi pelajaran. Penelitian ini mengungkap bahwa pemikiran KH. M. Hasyim Asy‘ari tentang pendidikan karakter selaras bahkan mendahului sejumlah nilai dalam materi pendidikan karakter dari Badan Penelitian dan Pengembangan, Pusat Kurikulum Kementerian Pendidikan Nasional, Indonesia, sehingga bisa dikembangkan dalam wacana pendidikan karakter yang sedang marak dilakukan dan bisa mencetak peserta didik yang tidak hanya berilmu luas tetapi juga berkarakter]